Aeroallergen sensitization predicts acute chest syndrome in children with sickle cell anaemia. (24th January 2018) - Willen, Shaina M.; Rodeghier, Mark; Strunk, Robert C.; Bacharier, Leonard B.; Rosen, Carol L.; Kirkham, Fenella J.; DeBaun, Michael R.; Cohen, Robyn T.
Summary: Asthma is associated with higher rates of acute chest syndrome (ACS) and vaso‐occlusive pain episodes among children with sickle cell anaemia (SCA). Aeroallergen sensitization is a risk factor for asthma. We hypothesized that aeroallergen sensitization is associated with an increased incidence of hospitalizations for ACS and pain. Participants in a multicentre, longitudinal cohort study, aged 4–18 years with SCA, underwent skin prick testing to ten aeroallergens. ACS and pain episodes were collected from birth until the end of the follow‐up period. The number of positive skin tests were tested for associations with prospective rates of ACS and pain. Multivariable models demonstrated additive effects of having positive skin tests on future rates of ACS (incidence rate ratio (IRR) for each positive test 1·23, 95% confidence interval [CI] 1·11–1·36, P  < 0·001). Aeroallergen sensitization was not associated with future pain (IRR 1·14, 95%CI 0·97–1·33, P  = 0·11). Our study demonstrated that children with SCA and aeroallergen sensitization are at increased risk for future ACS. Future research is needed to determine whether identification of specific sensitizations and allergen avoidance and treatment reduce the risk of ACS for children with SCA.